Effectiveness of Ginger Ointment (Zingiber officinale roscoe) on Incision Wound Healing in White Rats (Rattus norvegicus) - Abdul Wahid Jamaluddin; Ayu Lestari; Wa Ode Santa Monica (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2021)
Ginger (Zingiber officinale roscoe) is one of the most popular plants to be processed into herbal medicine. This plant contains active compounds in the form of gingerols, shogaols, flavonoids and saponins, which have anti-inflammatory, anti-tumor, antioxidant and antimicrobial effects. This study aims to determine the effectiveness of ginger extract ointment on incision wound healing time in white rats (Rattus norvegicus) by observing the percentage of wound healing and changes in wound morphology. This study used a laboratory experimental method using 24 white rats as test animals which were divided into four groups, namely two treatment groups (10% and 20% ginger extract ointment) and two control groups (one negative control group (no treatment) and one positive control group (Oxyfresh Soothing Pet Gel®)). The rats were anesthetized and shaved, then an incision was made on the dorsal part of the rat. The treatment was given twice a day for 14 days. The results showed that there were differences in the comparison of the percentage of wound area between the negative control group (without treatment), the positive control (Oxyfresh Soothing Pet Gel®), the treatment groups (ginger extract ointment 10% and 20%). The conclusion of the study was that the treatment group with 10% ginger extract ointment was more effective in accelerating the wound healing process. Keywords: Ginger extract,  Incision, wound healing, ointment, white rat.